2019
DOI: 10.1002/anie.201902961
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐Surface Engineering by Decorating Metal‐Oxo Nodes with Phenylsilane to Give Versatile Super‐Hydrophobic Metal–Organic Frameworks (MOFs)

Abstract: Hydrophobization of metal-organic frameworks (MOFs) is important to push forwardt heir practical use and thus has attracted increasing interest. In contrast to the previous reports,w hich mainly focused on the modification of organic ligands in MOFs,h erein, we reported an ovel strategy to decorate the metal-oxo nodes of MOFs with phenylsilane to affords uper-hydrophobic NH 2 -UiO-66(Zr), which shows highly improved base resistance and holds great promise in versatile applications,s uch as organic/water separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 60 publications
(122 reference statements)
1
43
0
Order By: Relevance
“…The results also proved that the NMOF‐1 coating was stable to acidic (pH: 1–6), weakly basic (pH: ≤ 9), and high‐ionic‐strength aqueous solutions, as suggested by the slight change in contact angles among the surfaces. A similar self‐cleaning property was also demonstrated for a superhydrophobic MOF (water contact angle: 161°), UiO‐66‐NH 2 ‐shp, which was obtained by reacting phenylsilane with the hydroxyl groups in the Zr 6 O 4 (OH) 4 clusters of UiO‐66‐NH 2 …”
Section: Potential Applicationssupporting
confidence: 55%
See 2 more Smart Citations
“…The results also proved that the NMOF‐1 coating was stable to acidic (pH: 1–6), weakly basic (pH: ≤ 9), and high‐ionic‐strength aqueous solutions, as suggested by the slight change in contact angles among the surfaces. A similar self‐cleaning property was also demonstrated for a superhydrophobic MOF (water contact angle: 161°), UiO‐66‐NH 2 ‐shp, which was obtained by reacting phenylsilane with the hydroxyl groups in the Zr 6 O 4 (OH) 4 clusters of UiO‐66‐NH 2 …”
Section: Potential Applicationssupporting
confidence: 55%
“…Instead of using the coordination bonding between open metal sites and hydrophobic terminal ligands, covalent bonding between inorganic SBUs and reactive species has also been applied to the hydrophobization of MOFs. Recently, Sun et al reported the hydrophobization of UiO‐66‐NH 2 (formulated as [Zr 6 O 4 (OH) 4 (1,4‐bdc‐NH 2 ) 6 ]) by the reaction of phenylsilane (PhSiH 3 ) with the hydroxyl groups on its Zr 6 O 4 (OH) 4 clusters ( Figure ) . While the pristine UiO‐66‐NH 2 showed a water contact angle of 0°, in contrast, a silylated sample of UiO‐66‐NH 2 (UiO‐66‐NH 2 ‐shp) showed a very high water contact angle of 161°, although, its BET surface area decreased from 974.4 m 2 g −1 to 656.5 m 2 g −1 .…”
Section: Preparation Of Hydrophobic Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design concept is also applicable to other TTA‐UC pairs and enables tuning of the UCL color, for example, by replacing DPA with other dyes as exemplarily shown for 2,5,8,11‐tetra‐ tert ‐butyl‐perylene, that yields UCL at 450 nm (Supporting Information, Figure S20). Current work aims to reduce the oxygen sensitivity and to increase the retention of the trapped annihilators in organic environments, for example, by tuning the chain length of the carboxylic acid and by coating the MOF surface . In addition, the TTA‐UC efficiency will be further enhanced by reducing the reabsorption of the UC emission caused by Pd(TCPP) and by optimizing the sensitizer/annihilator interface …”
Section: Figurementioning
confidence: 99%
“…Current work aims to reduce the oxygen sensitivity and to increase the retention of the trapped annihilators in organic environments, for example, by tuning the chain length of the carboxylic acid and by coating the MOF surface. [43] In addition, the TTA-UC efficiencyw ill be furthere nhanced by reducing the reabsorption of the UC emission caused by Pd(TCPP) and by optimizing the sensitizer/annihilator interface. [12,22,39,44,45]…”
mentioning
confidence: 99%